Hearing Disorders and Sensorineural Aging. (22nd January 2014) - Fioretti, Alessandra; Poli, Otello; Varakliotis, Theodoros; Eibenstein, Alberto
Abstract : The physiological age-related hearing loss is defined as presbycusis and it is characterized by reduced hearing sensitivity and problems in understanding spoken language especially in a noisy environment. In elderly the reduced speech recognition is generally caused by a reduction of the cochlear cells in the organ of Corti and degeneration of the central auditory pathways. In order to have a complete management strategy of central and peripheral presbycusis the diagnostic evaluation should include clinical ENT examination, standard audiological tests, and tests of central auditory function. Treatment should include not only the appropriate instruments for peripheral compensation but also auditory rehabilitative training and counseling to prevent social isolation and loss of autonomy. Other common hearing disorders in elderly are tinnitus and hyperacusis which are often undervalued. Tinnitus is characterized by the perception of a "phantom" sound due to abnormal auditory perception. Hyperacusis is defined as a reduced tolerance to ordinary environmental sounds. Furthermore auditory, visual, nociceptive, and proprioceptive systems may be involved together in a possible context of "sensorineural aging." The aim of this review is to underline the presence of hearing disorders like tinnitus and hyperacusis which in many cases coexist with hearing loss in elderly.